Colorectal tissue engineering: prerequisites, current status and perspectives. (July 2013) - Denost, Quentin; Adam, Jean-Philippe; Rullier, Eric; Bareille, Reine; Montembault, Alexandra; David, Laurent; Bordenave, Laurence
Gastrointestinal tissue engineering has emerged over the past 20 years and was often focused on esophagus, stomach or small intestine, whereas bioengineering researches of colorectal tissue are scarce. However, some promising results have been obtained in animal models. Refinements should be performed in scaffold and cell source selection to allow smooth muscle layer regeneration. Indeed, synthetic and natural polymers such as small intestinal submucosa and collagen sponge seeded with organoid units or smooth muscle cells did not allow smooth muscle regeneration. Mesenchymal stem cells derived from adipose tissue seeded on composite scaffold could represent an interesting way to achieve this goal. This article reviews potential indications, current status and perspectives of tissue engineering in the area of colorectal surgery.